08.37 Thrombospondin-1 is highly expressed by salivary gland epithelial cells of sjögren's syndrome patients, both constitutively and upon exposure to necrotic cells debris. (1st March 2017) - Vakrakou, Aglaia G; Patsouras, Markos D; Vlachoyiannopoulos, Panagiotis G; Tzioufas, Athanasios G; Manoussakis, Menelaos N
Abstract : Sjögren's syndrome (SS) patients manifest inflammation in salivary glands (SG) and evidence of intrinsic activation in the salivary gland epithelial cells (SGEC). Recent evidence from this laboratory has indicated that the aberrant exposure of SGEC of SS patients to necrotic debris may be a major cause of inflammatory reactions via activation of inflammasome. Thrombospondin (TSP-1) is a matricellular glycoprotein with proinflammatory, antiangiogenic and proapoptotic properties. It was originally characterised as an α-granule glycoprotein in platelets, although can be synthesised and released by a variety of cell types, including epithelial cells. Herein, we assessed the expression of TSP-1 in cultured ductal SGEC lines obtained from SS patients and controls. We also sought to investigate the effect of necrotic cell debris (NEC) on mRNA synthesis and release of TSP-1, in healthy epithelium. SS patients (n=14) displayed significant upregulation of TSP-1 mRNA levels in cultured SGEC compared to controls (n=10, p=0.0005), that correlated with the severity of histopathologic lesions (tarpley score of respective SG tissue biopsy) (Kruskal-Wallis test, p=0.001). SS-SGEC (n=16) were also found to secrete constitutively more TSP-1 and IL-1β in their culture supernatants, compared to non-SS SGEC (n=15) (p=0.0001 and p=0.06, respectively). There was a positive correlation among the constitutively expressed levels of TSP-1 and IL-1β (Spearman's r=0.66 for mRNA and r=0.41 for protein). Treatment of healthy SGEC lines (n=4) with NEC led to induction of TSP-1 and IL-1β mRNA (2.1-fold and 2-fold increase, respectively), as well as protein in culture supernatants (3.0-fold and 2.5-fold increase, respectively) (for all comparisons, p<0.05), that were abrogated upon pre-treatment of NEC with DNase1. Finally, immunohistochemistry analysis in SG revealed the overexpression of TSP-1 and IL-β, mainly in epithelial structures (both ductal and acinar cells) of SS patients, compared to non-SS controls. Preliminary results suggest for the first time that SGEC from SS patients manifest increased TSP-1 and IL-1β levels that correlate with severe lymphocytic infiltrates in SG. Chronic exposure to necrotic cells debris may hold a key pathogenetic role in the tissue inflammatory reactions of SS patients and may also explain the 'intrinsic activation status' that characterises the epithelia of these patients.